The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s00216-007-1595-2
|View full text |Cite
|
Sign up to set email alerts
|

Use of specific peptide biomarkers for quantitative confirmation of hidden allergenic peanut proteins Ara h 2 and Ara h 3/4 for food control by liquid chromatography–tandem mass spectrometry

Abstract: A liquid chromatography-electrospray-tandem mass spectrometry (LC-ESI-MS-MS) method based on the detection of biomarker peptides from allergenic proteins was devised for confirming and quantifying peanut allergens in foods. Peptides obtained from tryptic digestion of Ara h 2 and Ara h 3/4 proteins were identified and characterized by LC-MS and LC-MS-MS with a quadrupole-time of flight mass analyzer. Four peptides were chosen and investigated as biomarkers taking into account their selectivity, the absence of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 22 publications
0
56
0
Order By: Relevance
“…Previous characterization of Ara h 2 provided the identification of an N-terminal peptide [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and two tryptic peptides [82][83][84][85][86][87][88][89][90][91][92][93][94] and [95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110], which were proposed as potential biomarkers for regulatory monitoring. 6 A recent study of 2-D gel electrophoretic patterns of proteins from the Virginia type peanut identified fourteen spots that were linked to Ara h 2 by partial peptide mass fingerprinting. 7 In a separate study in 1992 focused on potential post-translational modifications (PTM), Burks et al proposed that Ara h 2 is a glycoprotein, based on periodic acid-Schiff staining.…”
Section: Introductionmentioning
confidence: 99%
“…Previous characterization of Ara h 2 provided the identification of an N-terminal peptide [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and two tryptic peptides [82][83][84][85][86][87][88][89][90][91][92][93][94] and [95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110], which were proposed as potential biomarkers for regulatory monitoring. 6 A recent study of 2-D gel electrophoretic patterns of proteins from the Virginia type peanut identified fourteen spots that were linked to Ara h 2 by partial peptide mass fingerprinting. 7 In a separate study in 1992 focused on potential post-translational modifications (PTM), Burks et al proposed that Ara h 2 is a glycoprotein, based on periodic acid-Schiff staining.…”
Section: Introductionmentioning
confidence: 99%
“…SRM is presently considered the gold standard for absolute quantification, whereas multiple reaction monitoring (MRM) can monitor the masses of selected signature peptides. For an allergen evaluation, internal reference peptides are required for food product monitoring by LC-SRM MS [124]. Hydrolyzed protein samples are spiked with known amounts of synthetic peptides and monitored by LC-MS in the SRM mode.…”
Section: Allergen Quantification Methodsmentioning
confidence: 99%
“…Table 4a. Quantification of food allergens in different food products by mass spectrometry using label-free quantification with an (1) external calibration curve [75][76][77][78][79]88], (2) unlabelled modified synthetic peptide [78], and (3) standard addition [79]. Table 4b.…”
Section: Quantifying Food Allergensmentioning
confidence: 99%
“…Using a calibration curve obtained by spiking fruit juice with extracted milk proteins, they found recoveries between 68 and 79% [75]. This strategy was also used to quantify peanut proteins in rice crispy/chocolate snacks [76]. A significant suppression effect, ranging from 30 to 50%, was observed for the Ara h2 peptide signal, while suppression of the Ara h3/4 peptide signal was less than 10%.…”
Section: Label-free Quantificationmentioning
confidence: 99%
See 1 more Smart Citation